PERLINDUNGAN HUKUM TERHADAP PEKERJA WANITA DAN ANAK DI INDONESIA - Fauzia Zainin (Ensiklopedia of Journal, 2022)
Article 1 of Law Number 13 of 2003 concerning Manpower states that, "A workforce is anyone who is able to do work to produce goods/or services both to meet their own needs and for the community". This understanding includes women and child workers. The purpose of this study was to determine the legal protection of female workers in terms of Law No. 13 of 2003 concerning Manpower and International Conventions, as well as the programs used to anticipate child labour. Based on the results of the discussion in this article, the author concludes that the laws and regulations made by the government regarding the protection of occupational safety and health are sufficient to regulate and provide protection for workers, especially female workers, namely providing women with unions and democracy in the workplace, protection of female workers against discrimination, protection of the fulfillment of workers' basic rights, protection of occupational safety and health; and urge people who are able to adopt street children, where street children are part of the community or citizens also have the same rights as other children, they have the right to education and welfare to live properly as members of society.